Evaluating the association between dietary salt intake and the risk of atrial fibrillation using Mendelian randomization - Wang, Sicen; Cheng, Ye; Zheng, Qi; Su, Xin; Deng, Yingjian (Frontiers in Nutrition, 2023)
Abstract Background: Previous studies have suggested that dietary salt intake affects atrial fibrillation (AF); however, the causal association between them still remains unclear. Thus, we conducted this Mendelian randomization (MR) study to explore the correlation between them. Methods: Genetic instruments for dietary salt intake were from a genome-wide association study (GWAS), which included 462,630 European individuals. Summary-level data for AF were obtained from another published GWAS (22,068 cases and 116,926 controls). The inverse-variance weighting (IVW) method was performed as the primary MR analysis. Multiple MR methods, including Robust Adjusted Profile Score (MR-RAPS), maximum likelihood estimation, and Mendelian randomization pleiotropy residual sum and outlier test (MR-PRESSO) were conducted as complementary analyses. The MR-Egger regression intercept and MR-PRESSO global test were conducted to test potential horizontal pleiotropy. The IVW (Q) method and MR-Egger were performed to detect heterogeneity. Results: Our results suggested that high dietary salt intake was significantly correlated with increased risk of AF (IVW: odds ratio [OR], 1.36; 95% confidence interval [CI], 1.04-1.77; P = 2.25E-02). The maximum likelihood estimation (OR, 1.37; 95% CI, 1.05-1.78; P = 2.09E-02), MR-RAPS (OR, 1.37; 95% CI, 1.03-1.81; P = 2.79E-02), and MR-PRESSO method (OR, 1.36; 95% CI, 1.05-1.76; P = 2.37E-02) also showed that dietary salt intake was significantly correlated with the risk of AF. Conclusion: The findings of this study provide robust evidence supporting the correlation between dietary salt intake and the risk of AF. Future studies are required to further clarify this relationship and translate the findings into clinical and public health practice.